UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA TEORI PROGRAM LINIER DENGAN MENGGUNAKAN METODE PROBLEM SOLVING DI SMK NURUL HIDAYAH PASUNDAN CIANJUR - Ratnasari Ratnasari; Luvy Sylviana Zanthy (Journal on Education, 2019)
The background of this research is the lack of mathematics learning outcomes of students at Nurul Hidayah Pasundan Vocational School on Linear Program material. This research was conducted in 3 cycles, while the data taken was the results of student replication data per cycle. In each cycle 3 steps of the study are carried out, namely planning, implementation, and continuous reflection. From the results of the test 1 cycle students obtained an average value of 52, learning completeness 39%, students divided into 3 groups, who mastered the material, only partially mastered, and who did not master the material. In cycle 2 the average score is 60, learning accuracy is 61%, until the end of cycle 3 the average results are 67, learning completeness is 82%. From the results of the end of cycle 3, the students' scores tend to be evenly distributed which meet the minimum criteria for accuracy.